Crystallization and preliminary X-ray diffraction analysis of a glutathione S-transferase from Xylella fastidiosa - Garcia, Wanius; Travensolo, Regiane F.; Rodrigues, Nathalia C.; Muniz, Joao R. C.; Caruso, Celia S.; Lemos, Eliana G. M. [UNESP]; Araujo, Ana Paula U.; Carrilho, Emanuel (Blackwell Publishing, 2008)
Glutathione S-transferases (GSTs) form a group of multifunctional isoenzymes that catalyze the glutathione-dependent conjugation and reduction reactions involved in the cellular detoxification of xenobiotic and endobiotic compounds. GST from Xylella fastidiosa (xfGST) was overexpressed in Escherichia coli and purified by conventional affinity chromatography. In this study, the crystallization and preliminary X-ray analysis of xfGST is described. The purified protein was crystallized by the vapour-diffusion method, producing crystals that belonged to the triclinic space group P1. The unit-cell parameters were a = 47.73, b = 87.73, c = 90.74 angstrom, alpha = 63.45, beta = 80.66, gamma = 94.55 degrees. xfGST crystals diffracted to 2.23 angstrom resolution on a rotating-anode X-ray source.